Modeling and Analyzing Documentation Supply Chain Within Customer Delivery Projects - Hietakangas, Leena (My University, 2015)
A large amount of documentation is produced and distributed to support the design, delivery and operation of a power plant. The documents and related information, such as delivery data, flow through a supply chain which involves several functions in different companies. Multiple processes and activities are carried out to create and deliver documentation. Several software applications are used within the chain to manage the documents and related information. Changes in organizations, processes, software applications and other subjects within the chain will affect the supply of documents and the information flow. In short, the document delivery chain is a complex entity, which crosses organizational boundaries and is influenced by changes. Hence, it is difficult to manage as a whole. The purpose of this thesis is to model and analyze the documentation supply chain and the flow of related information within customer delivery projects. The research is related to several development projects that are ongoing within the case company. This thesis is part of master’s degree studies in Industrial Management. The topic was assigned by the documentation organization within the case company. The report begins by introducing the related background theory and by describing the company’s project environment and documentation procedures. The different functions within the delivery chain are presented in detail. Process flowcharts for each function of the delivery chain and an accompanying handbook were created and attached to this report. They can be used as a reference when the various processes within the delivery chain are presented or analyzed. Interview findings, especially improvement opportunities within the chain, are listed and analyzed with the aid of background theory. The following questions will be answered: How to ensure correct and timely delivery of documents so that they are available when needed? How to share information in a sufficient manner, so that all parties will have an easy access to information they need? How to make the documentation supply chain efficient and create value? The issues discussed include for example: delivery follow-up and evidence, communication, way of working, and the development of supporting software applications.
Keywords: Technical documentation; document management; process modeling; quality management; logistics; supply chain management; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|